Endophytic Fungi from Aegle marmelos Plant: A Potent and Innovative Platform for Enhanced Cellulolytic Enzyme Production - Badiya, Pradeep Kumar; Thota, Sai Praneeth; Yerram, Sandeep; Vadlani, Praveen V.; Vedantam, Pallavi; Ramamurthy, Sai Sathish; Golakoti, Nageswara Rao; Sharma, Robin; Kumar, B.S. Vijaya (Journal of Technology Innovations in Renewable Energy, 2018)
Fungi have a prominent status in fermentation for the production of different bio-products. Endophytic fungi isolated from medicinal plants are particularly formidable in their adaptability to solid state fermentation as an extension of its natural habitat and are also a potent source of broad-spectrum cellulolytic enzymes. We report for the first time the use of endophytic fungus isolated from Aegle marmelos for enhanced cellulolytic enzymes production from groundnut shell (GNS) as substrate. ImageJ software identified Trichoderma harzianum as an endophytic fungus having maximum radial growth rate. A systematic comparison of the endophytic fungus with Aspergillus oryzae, under solid state fermentation (SSF) and submerged fermentation (SmF) conditions was performed and enhanced cellulase production was observed by the endophytic fungus (4.27 FPU/ml) under SSF environment compared to SmF (2.35 FPU/ml). A comprehensive understanding of the systemic breakdown in the structural integrity of the biomass has been achieved using a synergy of enzyme assay protocols, spectral and thermal based techniques. The use of endophytic fungi in SSF systems in our study lays the basis for the production of other industrially important enzymes. The present study opens the door for the synergistic use of endophytic and epiphytic fungi for the production of cellulolytic enzyme.